Enhancing Counselor Education and Supervision through Deliberate Practice - Zach Budesa; Casey A Barrio Minton (Teaching and Supervision in Counseling, 2022)
Abstract: Professional and student counselors must develop and maintain their counseling skills in order to engage in ethical and effective counseling. Recent research suggests that graduate education and supervision has little effect on client outcomes. Investigations of expertise development have given rise to deliberate practice, a framework which structures skill development research and instruction. Deliberate practice involves individualized coaching, repetition, and solo practice in development of optimal performance. This conceptual article introduces deliberate practice as a framework for enhancing effectiveness of counselor education and supervision practices. Applications of deliberate practice to teaching and supervision and suggestions for future research are provided. What is the public significance of this article?: Counseling pedagogy uses a variety of methods in classrooms and supervision to help novice counselors develop key skills for their work. Deliberate Practice may be an effective method to help counselors develop more effective skills for working with their clients. Deliberate Practice provides a unified framework to help integrate common methods across teaching and supervision, and emphasizes the use of repetitive practice and individualized feedback.
Keywords: Deliberate Practice; Skill Development; Counselor Education